RACE, CODE OF THE STREET, AND VIOLENT DELINQUENCY: A MULTILEVEL INVESTIGATION OF NEIGHBORHOOD STREET CULTURE AND INDIVIDUAL NORMS OF VIOLENCE - Stewart, Eric A. (2010)
The study outlined in this article drew on Elijah Anderson’s (1999) code of the street perspective to examine the impact of neighborhood street culture on violent delinquency. Using data from more than 700 African American adolescents, we examined 1) whether neighborhood street culture predicts adolescent violence above and beyond an adolescent’s own street code values and 2) whether neighborhood street culture moderates individual-level street code values on adolescent violence. Consistent with Anderson’s hypotheses, neighborhood street culture significantly predicts violent delinquency independent of individual-level street code effects. Additionally, neighborhood street culture moderates individual-level street code values on violence in neighborhoods where the street culture is widespread. In particular, the effect of street code values on violence is enhanced in neighborhoods where the street culture is endorsed widely.